A method for preparing a polyanion positive electrode material
Through the recycling and processing of retired lithium iron phosphate batteries, a positive electrode material of polyanionic sodium ion battery with excellent performance was prepared, which solved the problems of resource waste and environmental pollution, improved the specific capacity and conductivity of the materials, and realized sodium ion battery efficient preparation.
Patent Information
- Application Number
- CN202210154339.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-02-18
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2042-02-18
AI Technical Summary
The treatment problems of a large number of retired lithium iron phosphate batteries have led to waste of resources and environmental pollution, and lithium resources are tight. It is necessary to find a recycling method to prepare the positive electrode material of sodium ion battery with excellent performance.
By crushing lithium iron phosphate batteries, soaking acid liquid, removing copper, adjusting element content, oxidizing, calcining and alkali treatment, polyanionic positive electrode material is prepared and sintered with sodium and carbon sources to form NaFePO4/C material. Co-precipitation of aluminum and iron is used to generate atomic vacancies to improve specific capacity and conductivity.
It realizes the reuse of waste battery resources, saves resources, improves the performance of the positive electrode material of sodium ion battery, solves the preparation problem caused by the large sodium ion radius, and does not need to remove aluminum first, and optimizes the process flow.
Smart Images

Figure CN114744165B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of energy storage materials, and in particular relates to a method for preparing a polyanion positive electrode material. Background Art
[0002] With the rise of electric vehicles, the demand for power batteries is increasing. Among them, lithium iron phosphate batteries are one of the important power batteries. However, with the use and consumption of electric vehicles, the amount of retired batteries will also increase day by day, especially after many years, a large number of lithium iron phosphate batteries will be retired. If a large number of retired power lithium iron phosphate batteries cannot be properly recycled and utilized, it will not only waste resources, but also bring about environmental pollution and other problems. Therefore, how to better deal with retired lithium iron phosphate batteries has become an urgent problem that the industry needs to solve.
[0003] Lithium resources on the earth are very limited. As lithium resources become increasingly scarce, sodium, which has abundant reserves, has come into people's view. Sodium and lithium are in the same main group and have similar chemical properties. The content of sodium in the earth's crust is much higher than that of lithium. Therefore, sodium-ion batteries are a very promising secondary battery. At present, common positive electrode materials for sodium-ion batteries mainly include layered transition metal oxides, Prussian blue analogs, polyanion compounds, tunnel-type oxides, etc. Polyanion compounds mainly include transition metal (pyro) phosphates, fluorophosphates, etc. Among them, polyanion phosphate materials may become one of the ideal positive electrode materials for sodium-ion batteries due to their stable structure and high operating voltage. Recycling waste lithium batteries to prepare sodium-ion batteries is a direction with great development prospects.
[0004] Therefore, there is an urgent need to provide a recycling method that can recycle lithium iron phosphate batteries and prepare them into sodium ion battery positive electrode materials with excellent performance. Summary of the invention
[0005] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention proposes a method for preparing a polyanion positive electrode material, which recycles waste lithium iron phosphate batteries to prepare a polyanion positive electrode material, which can be applied to secondary batteries, so that the resources in the waste batteries can be reused, which is beneficial to resource conservation and environmental protection.
[0006] The first aspect of the present invention provides a method for preparing a polyanionic positive electrode material.
[0007] Specifically, a method for preparing a polyanionic cathode material comprises the following steps:
[0008] (1) crushing the lithium iron phosphate battery into battery powder, adding acid solution to soak, and then separating the solid and liquid to obtain a leachate;
[0009] (2) removing copper from the leaching solution prepared in step (1), and then adjusting the contents of phosphorus, iron and aluminum in the leaching solution to obtain an adjusted solution;
[0010] (3) adding an oxidant to the adjusted solution prepared in step (2), adjusting the pH value to 1.8-2.8, and performing solid-liquid separation to obtain a precipitate;
[0011] (4) calcining the precipitate prepared in step (3), and then soaking it in an alkali solution; mixing the soaked precipitate with a sodium source and a carbon source, drying, and sintering to obtain the polyanionic positive electrode material.
[0012] Preferably, in step (1), the acid solution is selected from at least one of sulfuric acid, hydrochloric acid or phosphoric acid.
[0013] Preferably, in step (1), the mass concentration of the acid solution is 10%-50%; further preferably, the mass concentration of the acid solution is 20%-40%.
[0014] Preferably, in step (1), the solid-liquid ratio of the acid solution to the battery powder is 1-10 mL: 1 g; further preferably, in step (1), the solid-liquid ratio of the acid solution to the battery powder is 2-5 mL: 1 g.
[0015] Preferably, in step (1), the soaking temperature is 30-100°C; the soaking time is 1-10 hours; further preferably, in step (1), the soaking temperature is 40-90°C; the soaking time is 2-8 hours.
[0016] Preferably, in step (2), the method for removing copper from the leaching solution prepared in step (1) is to add a copper removing agent to the leaching solution.
[0017] Preferably, the copper removing agent is iron powder and / or aluminum powder.
[0018] Preferably, in step (2), the contents of phosphorus, iron and aluminum in the leachate are adjusted by adding aluminum salts, phosphates and soluble trivalent iron salts.
[0019] Preferably, in step (2), the molar ratio of iron, aluminum and phosphorus in the adjustment solution is x:y:(1.0-1.1), wherein x+y=1, x>0, y>0.
[0020] Preferably, in step (3), the oxidant is selected from at least one of hydrogen peroxide, oxygen, chlorine, sodium chlorate or hypochlorous acid.
[0021] Preferably, in step (3), the pH value is adjusted to 2.0-2.5 at a temperature of 75-95° C. If the pH value is too low, complete precipitation will not occur; and if the pH value is too high, hydroxide will be generated.
[0022] Preferably, in step (3), a separated liquid is obtained after the solid-liquid separation, and the separated liquid is a lithium-containing solution. The separated liquid can be further purified to prepare lithium salt, so that lithium can be recovered, thereby solving the problem of lithium resource shortage.
[0023] Preferably, in step (4), the calcination temperature is 500-800° C., and the calcination time is 3-6 hours.
[0024] Preferably, in step (4), the alkali solution is a sodium hydroxide solution or a potassium hydroxide solution.
[0025] Preferably, the concentration of the sodium hydroxide solution is 0.05-4.0 mol / L; further preferably, the concentration of the sodium hydroxide solution is 0.1-1.0 mol / L. For example, 0.05, 0.1, 0.15, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.5, 2.0, 2.5, 3.0, 4.0 mol / L are selected. The precipitation is treated with a sodium hydroxide solution, wherein aluminum phosphate is dissolved in the sodium hydroxide solution to generate sodium tetrahydroxyaluminate and sodium phosphate. If the concentration of sodium hydroxide is too low, the reaction will be slow and the efficiency will be low; if the concentration is too high, it will easily lead to the transformation of iron phosphate into iron hydroxide.
[0026] Preferably, in step (4), the soaking time is 0.1-3.0 h; further preferably, in step (4), the soaking time is 0.1-2.0 h.
[0027] Preferably, in step (4), water is added during the mixing process.
[0028] Preferably, in step (4), the sodium source is selected from at least one of sodium carbonate, sodium acetate or sodium oxalate.
[0029] Preferably, in step (4), the carbon source is selected from at least one of glucose, citric acid, oxalic acid, lactose or galactose.
[0030] Preferably, in step (4), the molar ratio of the sodium element in the sodium source to the phosphorus element in the precipitate is (0.1-1.5):1; further preferably, in step (4), the molar ratio of the sodium element in the sodium source to the phosphorus element in the precipitate is (0.3-1):1.
[0031] Preferably, in step (4), the ratio of the amount of the carbon source to the amount of phosphorus in the precipitate is (0.5-3):1; further preferably, in step (4), the ratio of the amount of the carbon source to the amount of phosphorus in the precipitate is 1-2:1.
[0032] Preferably, in step (4), the sintering process is sintering at 500-700°C for 5-10 hours under a protective atmosphere; further preferably, in step (4), the sintering process is sintering at 550-650°C for 6-10 hours under a protective atmosphere.
[0033] Preferably, the polyanion positive electrode material prepared by the preparation method is a polyanion positive electrode material for sodium ion batteries.
[0034] The second aspect of the present invention provides an application of a method for preparing a polyanionic positive electrode material.
[0035] Specifically, a method for preparing a polyanion positive electrode material is used in preparing a battery.
[0036] Preferably, the battery is a sodium ion battery.
[0037] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0038] (1) The present invention recycles waste lithium iron phosphate batteries to prepare polyanion positive electrode materials, which can be applied to secondary batteries, so that the resources in the waste batteries can be reused, which is beneficial to resource conservation and environmental protection.
[0039] (2) The preparation method of the polyanionic positive electrode material provided by the present invention comprises the following steps: crushing, acid-lyzing, removing copper, adjusting the element content, and oxidizing the waste lithium iron phosphate battery; adjusting the pH value to 1.8-2.8, while generating iron phosphate, aluminum is co-precipitated with the iron phosphate in the form of aluminum phosphate, and the iron and aluminum are uniformly mixed in the crystal structure of the precipitate; then calcining the precipitate, soaking it in alkaline solution (sodium hydroxide) to remove aluminum, and dissolving the aluminum in the crystal in the form of sodium tetrahydroxyaluminate in the solution, thereby obtaining atomic vacancies, which are beneficial to the subsequent embedding of sodium ions and carbon elements during sintering with a sodium source and a carbon source, further improving the specific capacity and conductivity of the material, thereby solving the problem that the sodium ion radius is large and it is difficult to de-embed when preparing the positive electrode material.
[0040] (3) The preparation method of the polyanionic positive electrode material provided by the present invention is different from other battery recycling processes and positive electrode material preparation methods. In the leaching solution obtained by acid hydrolysis, there is no need to remove aluminum first, but it can be used for valuable purposes. Aluminum and iron are first co-precipitated and mixed, and then aluminum is removed to obtain atomic vacancies, which is conducive to the subsequent embedding of sodium ions and carbon elements. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 The process flow chart of preparing the polyanion positive electrode material in Example 1;
[0042] Figure 2 This is the SEM image of the polyanionic positive electrode material prepared in Example 1. DETAILED DESCRIPTION
[0043] In order to make the technical scheme of the present invention more clearly understood by those skilled in the art, the following embodiments are listed for illustration. It should be pointed out that the following embodiments do not limit the protection scope of the present invention.
[0044] Unless otherwise specified, the raw materials, reagents or devices used in the following examples can be obtained from conventional commercial sources or by existing known methods.
[0045] Example 1
[0046] A method for preparing a polyanion positive electrode material, wherein the polyanion positive electrode material is prepared from waste lithium batteries, and the process flow chart is as follows Figure 1 As shown, the following steps are included:
[0047] (1) crushing the lithium iron phosphate battery and collecting the battery powder, then adding a sulfuric acid solution with a mass concentration of 40% to the collected battery powder at a liquid-solid ratio of 2 mL:1 g, and soaking for 8 hours at a temperature of 40° C.; after the reaction between the battery powder and the sulfuric acid solution is completed, filtering, solid-liquid separation to obtain a leachate and a leach residue;
[0048] (2) adding iron powder to the leaching solution, filtering to obtain a copper-removed solution; then detecting the contents of phosphorus, iron, and aluminum in the copper-removed solution, and adding soluble trivalent iron salt, aluminum salt, and phosphate to adjust the ratio of the amount of iron, aluminum, and phosphorus to 0.95:0.05:(1.0-1.1) to obtain an adjusted solution;
[0049] (3) adding hydrogen peroxide to the adjusted solution, controlling the temperature to 75-95° C., and slowly adding sodium hydroxide solution to adjust the pH value to 2.3 to generate precipitation; then filtering the precipitate, and obtaining a precipitate after solid-liquid separation;
[0050] (4) The precipitate was calcined at 550°C for 6 hours, and then soaked in a sodium hydroxide solution with a concentration of 0.1 mol / L for 2.0 hours; then, the soaked precipitate, sodium carbonate and glucose were added into deionized water according to the molar ratio of glucose, sodium carbonate and phosphorus in the precipitate of 1:0.5:1, and the mixture was fully mixed and stirred in a mixing tank, and then spray-dried and sintered at 550°C in a nitrogen atmosphere for 10 hours, and crushed to obtain a polyanionic positive electrode material with a chemical formula of NaFePO4 / C. The SEM image of the polyanionic positive electrode material prepared in Example 1 is shown in FIG. Figure 2 shown.
[0051] This positive electrode material is mainly used in sodium ion batteries.
[0052] Example 2
[0053] A method for preparing a polyanion positive electrode material comprises the following steps:
[0054] (1) crushing the lithium iron phosphate battery and collecting the battery powder, then adding a sulfuric acid solution with a mass concentration of 25% to the collected battery powder at a liquid-solid ratio of 3 mL:1 g, and soaking for 6 hours at a temperature of 50° C.; after the reaction between the battery powder and the sulfuric acid solution is completed, filtering, solid-liquid separation to obtain a leachate and a leach residue;
[0055] (2) adding iron powder to the leaching solution, filtering to obtain a copper-removed solution; then detecting the contents of phosphorus, iron, and aluminum in the copper-removed solution, and adding soluble trivalent iron salt, aluminum salt, and phosphate to adjust the amount of iron, aluminum, and phosphorus to a ratio of 0.90:0.1:1.0 to obtain an adjusted solution;
[0056] (3) adding sodium chlorate to the adjusted solution, controlling the temperature at 75-95° C., and slowly adding sodium hydroxide solution to adjust the pH value to 2.5 to generate precipitation; then filtering the precipitation, and obtaining a precipitate after solid-liquid separation;
[0057] (4) The precipitate is calcined at 680°C for 5 hours, and then soaked in a sodium hydroxide solution with a concentration of 0.5 mol / L for 1.0 hour; then, the soaked precipitate, sodium acetate and glucose are added to deionized water according to the molar ratio of glucose, sodium acetate and phosphorus in the precipitate being 1:1:1, and the mixture is fully mixed and stirred in a mixing tank, and then spray-dried and sintered at 580°C in an inert atmosphere for 9 hours, and crushed to obtain a polyanion positive electrode material with a chemical formula of NaFePO4 / C. The positive electrode material is mainly used in sodium ion batteries.
[0058] Example 3
[0059] A method for preparing a polyanion positive electrode material comprises the following steps:
[0060] (1) crushing the lithium iron phosphate battery and collecting the battery powder, then adding a sulfuric acid solution with a mass concentration of 20% to the collected battery powder at a liquid-solid ratio of 5 mL:1 g, soaking for 2 hours, and controlling the temperature during soaking to be 90° C.; after the battery powder and the sulfuric acid solution react, filtering, solid-liquid separation to obtain a leachate and a leach residue;
[0061] (2) adding iron powder to the leaching solution, filtering to obtain a copper-removed solution; then detecting the contents of phosphorus, iron, and aluminum in the copper-removed solution, and adding soluble trivalent iron salt, aluminum salt, and phosphate to adjust the molar ratio of iron, aluminum, and phosphorus to 0.93:0.07:1.0 to obtain an adjusted solution;
[0062] (3) adding hypochlorous acid to the adjusted solution, controlling the temperature at 75-95° C., slowly adding sodium hydroxide solution to adjust the pH value to 2.2 to generate precipitation; then filtering the precipitation, and obtaining a precipitate after solid-liquid separation;
[0063] (4) The precipitate is calcined at 800°C for 3 hours, and then soaked in a sodium hydroxide solution with a concentration of 1.0 mol / L for 0.1 hour; then, the soaked precipitate, oxalic acid, and sodium oxalate are added into deionized water according to the molar ratio of oxalic acid, sodium oxalate, and phosphorus in the precipitate of 1:0.5:1, and the mixture is fully mixed and stirred in a mixing tank, and then spray-dried, sintered at 650°C in an inert atmosphere for 6 hours, and crushed to obtain a polyanion positive electrode material with a chemical formula of NaFePO4 / C. The positive electrode material is mainly used for sodium ion batteries.
[0064] Example 4
[0065] A method for preparing a polyanion positive electrode material comprises the following steps:
[0066] (1) crushing the lithium iron phosphate battery and collecting the battery powder, then adding a sulfuric acid solution with a mass concentration of 30% to the collected battery powder at a liquid-solid ratio of 3 mL:1 g, and soaking for 2 hours at a temperature of 90° C.; after the reaction between the battery powder and the sulfuric acid solution is completed, filtering, solid-liquid separation to obtain a leachate and a leach residue;
[0067] (2) adding iron powder to the leaching solution, filtering to obtain a copper-removed solution; then detecting the contents of phosphorus, iron, and aluminum in the copper-removed solution, and adding soluble trivalent iron salt, aluminum salt, and phosphate to adjust the molar ratio of iron, aluminum, and phosphorus to 0.96:0.04:1.1 to obtain an adjusted solution;
[0068] (3) adding chlorine gas to the adjusted solution, controlling the temperature to 75-95° C., and slowly adding sodium hydroxide solution to adjust the pH value to 2.3 to generate precipitation; then filtering the precipitation, and obtaining a precipitate after solid-liquid separation;
[0069] (4) The precipitate is calcined at 600°C for 5 hours, and then soaked in a 0.2 mol / L sodium hydroxide solution for 0.1 hour; then, the soaked precipitate, glucose, and sodium acetate are added to deionized water according to the molar ratio of glucose, sodium acetate, and phosphorus in the precipitate of 1:0.7:1, and the mixture is fully mixed and stirred in a mixing tank, and then spray-dried, sintered at 650°C in an inert atmosphere for 7 hours, and crushed to obtain a precipitate with the chemical formula of Na 0.7 FePO4 / C polyanion positive electrode material. This positive electrode material is mainly used in sodium ion batteries.
[0070] Example 5
[0071] A method for preparing a polyanion positive electrode material comprises the following steps:
[0072] (1) crushing the lithium iron phosphate battery and collecting the battery powder, then adding a sulfuric acid solution with a mass concentration of 20% to the collected battery powder at a liquid-solid ratio of 4 mL:1 g, soaking for 4 hours, and controlling the temperature during soaking to be 60° C.; after the reaction between the battery powder and the sulfuric acid solution is completed, filtering, and solid-liquid separation to obtain a leachate and a leach residue;
[0073] (2) adding iron powder to the leaching solution, filtering to obtain a copper-removed solution; then detecting the contents of phosphorus, iron, and aluminum in the copper-removed solution, and adding soluble trivalent iron salt, aluminum salt, and phosphate to adjust the molar ratio of iron, aluminum, and phosphorus to 0.98:0.02:1.1 to obtain an adjusted solution;
[0074] (3) adding hypochlorous acid to the adjusted solution, controlling the temperature at 75-95° C., and slowly adding sodium hydroxide solution to adjust the pH value to 2.5 to generate precipitation; then filtering the precipitation, and obtaining a precipitate after solid-liquid separation;
[0075] (4) The precipitate is calcined at 550°C for 6 hours, and then soaked in a 0.1 mol / L sodium hydroxide solution for 0.1 hour; then, the soaked precipitate, lactic acid, and sodium carbonate are added to deionized water in a mixing tank according to the molar ratio of lactic acid, sodium carbonate, and phosphorus in the precipitate of 1:0.33:1, and the mixture is fully mixed and stirred in a mixing tank, and then spray-dried and sintered at 650°C in an inert atmosphere for 10 hours, and crushed to obtain a precipitate with a chemical formula of Na 0.66 FePO4 / C polyanion positive electrode material. This positive electrode material is mainly used in sodium ion batteries.
[0076] Comparative Examples 1-5
[0077] Comparative Examples 1-5 all adopt the conventional solid-phase method to prepare sodium iron phosphate polyanion positive electrode materials, which correspond to Examples 1-5 respectively. According to the molar ratio of sodium, iron, vanadium, phosphorus and carbon source of the sodium iron phosphate obtained in Examples 1-5, the carbon source, sodium source, phosphorus source and iron source are taken, mixed, and calcined under the same conditions as the corresponding examples to obtain sodium iron phosphate polyanion positive electrode materials with the same chemical formula.
[0078] Product effect testing
[0079] Take the sodium iron phosphate polyanion positive electrode materials prepared in Examples 1-5 and Comparative Examples 1-5 respectively, use N-methylpyrrolidone as solvent, mix the sodium iron phosphate polyanion positive electrode materials with acetylene black and PVDF in a mass ratio of 8:1:1, apply it on aluminum foil, dry it with air at 60-80℃ for 8h, and then vacuum dry it at 100-120℃ for 12h. The sodium iron phosphate positive electrode plate is obtained. In an argon-protected glove box, a metal sodium sheet is used as the negative electrode of the counter electrode and 1 mol / L NaPF6 is used as the electrolyte to assemble a CR2032 button battery. The rate performance of each CR2032 button battery is tested at 25℃, and the rate performance is (1C=155mAhg -1) Set the magnification and the results are shown in Table 1.
[0080] Table 1
[0081]
[0082]
[0083] As can be seen from Table 1, the battery assembled using the polyanion type positive electrode material prepared by the present invention has good performance, which is significantly better than the sodium iron phosphate polyanion type positive electrode material prepared by the solid phase method.
Claims
1. A method for preparing a polyanionic positive electrode material, characterized in that: The following steps are involved: (1) crushing the lithium iron phosphate battery into battery powder, adding acid solution to soak, and then separating the solid and liquid to obtain the leachate; (2) removing copper from the leaching solution prepared in step (1), and then adjusting the contents of phosphorus, iron and aluminum in the leaching solution to obtain an adjusted solution; (3) adding an oxidant to the adjusted solution prepared in step (2), adjusting the pH value to 2.2-2.8 at a temperature of 75-95° C., and performing solid-liquid separation to obtain a precipitate; (4) calcining the precipitate prepared in step (3), and then soaking it in an alkali solution to remove aluminum; then mixing the soaked precipitate with a sodium source and a carbon source, drying it, and sintering it to obtain a polyanion type sodium ion battery positive electrode material; In step (2), the molar ratio of iron, aluminum and phosphorus in the adjustment solution is x:y:(1.0-1.1), wherein x+y=1, x>0, y>0.
2. The preparation method according to claim 1, characterized in that: In step (2), the method for removing copper from the leaching solution prepared in step (1) is to add a copper removing agent to the leaching solution; the copper removing agent is iron powder and / or aluminum powder.
3. The preparation method according to any one of claims 1-2, characterized in that In step (4), the calcination temperature is 500-800°C, and the calcination time is 3-6 hours.
4. The preparation method according to any one of claims 1 to 2, characterized in that In step (4), the alkali solution is sodium hydroxide solution and / or potassium hydroxide; the concentration of the sodium hydroxide solution is 0.05-4.0 mol / L.
5. The preparation method according to any one of claims 1-2, characterized in that: In step (4), the soaking time is 0.1-3.0h.
6. The preparation method according to claim 1, characterized in that: In step (4), the molar ratio of the sodium element in the sodium source to the phosphorus element in the precipitate is (0.1-1.5):
1.
7. The preparation method according to claim 1, characterized in that: In step (4), the ratio of the amount of the carbon source to the amount of phosphorus in the precipitate is (0.5-3):
1.
8. The preparation method according to claim 6, characterized in that: In step (4), the sintering process is carried out under a protective atmosphere at 500-700° C. for 5-10 hours.
Citation Information
Patent Citations
Methods for preparing iron phosphate precursor and lithium iron phosphate positive electrode material
CN113942987A